On The History Of Nucleosynthesis And Creation Of Chemical Elements - Israilov M (Euro Asian Journal Publishing, 2024)
This article focuses on the evolutionary astrophysical history of the formation of all substances, celestial and earth bodies, and the entire universe, cited and analyzed the scientific astrophysical processes associated with these issues, nuclear reactions
Keywords: nucleosynthesis; nuclear reaction; s-process; r-process